DigitalVHI—a freeware open-source software application to capture the Voice Handicap Index and other questionnaire data in various languages. (July 2015) - Herbst, Christian T.; Oh, Jinook; Vydrová, Jitka; Švec, Jan G.
Abstract In this short report we introduce DigitalVHI, a free open-source software application for obtaining Voice Handicap Index (VHI) and other questionnaire data, which can be put on a computer in clinics and used in clinical practice. The software can simplify performing clinical studies since it makes the VHI scores directly available for analysis in a digital form. It can be downloaded from http://www.christian-herbst.org/DigitalVHI/